Channel Coordination and Quantity Discounts - Weng, Z. Kevin (Management Science, 1995)
This paper presents a model for analyzing the impact of joint decision policies on channel coordination in a system consisting of a supplier and a group of homogeneous buyers. The joint decision policy characterized by the unit selling price and the order quantity is coordinated through quantity discounts and franchise fees. Both the annual demand rate and the operating cost—including the purchase, ordering, and inventory holding costs—depend on the joint decision policy employed. This paper contributes by integrating work addressing quantity discounts on inventory and ordering policies and work focusing on the control mechanism provided by quantity discounts in channel coordination. It is shown that the optimal all-unit quantity discount policy is equivalent to the optimal incremental quantity discount policy in achieving channel coordination. Furthermore, it is shown that quantity discounts alone are not sufficient to guarantee joint profit maximization. The analyses of the general models are illustrated by specific analytical results obtained for a given demand function.